Digging Deeper to Save the Old Anti-tuberculosis Target: D-Alanine–D-Alanine Ligase With a Novel Inhibitor, IMB-0283 - Meng, Jianzhou; Gao, Peng; Wang, Xiao; Guan, Yan; Liu, Yishuang; Xiao, Chunling (Frontiers in Microbiology, 2020)
The emergence of drug-resistant Mycobacterium tuberculosis (Mtb) has hampered treatments for tuberculosis, which consequently now require novel agents to overcome such drug resistance. The genetically stable D-alanine–D-alanine ligase A (DdlA) has been deemed as an excellent therapeutic target for tuberculosis. In the present study, a competitive inhibitor (IMB-0283) of DdlA was obtained via high-throughput screening. The minimum inhibitory concentrations (MIC) of IMB-0283 for the standard and clinical drug-resistant Mtb strains ranged from 0.25–4.00 µg/mL, whereas the conventional inhibitor of DdlA, D-cycloserine (DCS), only inhibited the growth of the standard Mtb strain at 16 µg/mL. The lethal effect of IMB-0283 on Mtb was found to act intracellularly in a DdlA-dependent manner. Specifically, IMB-0283 prevented the synthesis of neonatal cell walls but did not damage mature cell walls. Compared with those of DCS, IMB-0283 exhibited lower cytotoxicity and a higher selective index (SI). At the same dosages of treatment, IMB-0283 reduced bacterial load (log CFU/mL) in an acute animal model from 5.58 to 4.40, while DCS did not yield any such treatment efficacy. Taken together, the lower cytotoxicity and more efficacious in vivo activity of IMB-0283 suggest that it is a promising lead compound for antituberculosis drug development.